2008
DOI: 10.1007/s11244-008-9142-8
|View full text |Cite
|
Sign up to set email alerts
|

Acylations with Long-Chain Acid Anhydrides and Acyl Chlorides over Zeolite Beta

Abstract: Acylation of ferrocene and toluene with linear, branched and aromatic anhydrides and chlorides of different chain length was investigated over zeolite Beta with Si/Al ratio 12.5. It was found that the conversion of ferrocene increased from acetic to butyric anhydride/chloride and then decreased with further increasing of chain length. The selectivity to 1-acylferrocene was in all cases 100%. In the case of toluene acylation, the conversions of acylating agent increased with the chain length of acylating agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The conversion of ferrocene in ferrocene acylation over zeolites is also influenced by the chain length of the acylating agent 104. Linear anhydrides and chlorides possessing an increasing number of carbon atoms in the chain and acylating agents with branched chains and aromatic part were studied.…”
Section: Acylation Of Ferrocenementioning
confidence: 99%
“…The conversion of ferrocene in ferrocene acylation over zeolites is also influenced by the chain length of the acylating agent 104. Linear anhydrides and chlorides possessing an increasing number of carbon atoms in the chain and acylating agents with branched chains and aromatic part were studied.…”
Section: Acylation Of Ferrocenementioning
confidence: 99%
“…Acylation of toluene and ferrocene with linear, branched and aromatic anhydrides over zeolite beta have also been investigated. 93 However, in these anhydride-related studies, the surface species was found to be similar to experiments using acetic acid as the reactant, so the reactive intermediates could not be elucidated. Regarding the nature of the active site, Wei et al 94 showed that in the acylation of anisole with acetic anhydride over Beta zeolite, the Brønsted acid sites played the predominant role, as opposed to the Lewis acid sites.…”
Section: Catalysis Science and Technology Minireviewmentioning
confidence: 87%
“…Zeolites are very interesting materials with mostly clearly defined crystal structures. Their roles in modern chemistry facilitate diverse applications such as catalysis, adsorption, and separation of gases. Zeolite β in particular has attracted great attention due to its relatively large pores and moderate acidity . The diverse experimental chemistry of this zeolite is in line with a variety of processes carried out .…”
Section: Introductionmentioning
confidence: 99%